Effect of storage temperature in various processing time on cytomorphological changes and cell count in sputum samples / Rifaatul Mahmudah Mohd Razemin - Mohd Razemin, Rifaatul Mahmudah (2015)
Background: Cytomorphological changes caused by exposure to storage temperature (2-8°C) in sputum samples can impact the interpretation of the laboratory results thus contribute to misdiagnosis in respiratory tract cytology. This study determined the effects of storage temperature in various processing time on the cytomorphology of sputum samples. Methods: 6 sputum samples were selected from healthy Universiti Teknologi MARA Puncak Alam campus students and sample were collected through deep cough method. Slides were prepared for cell count, Papanicolaou, May grunwald giemsa (MGG), and Gram stains from samples that were exposed to 2-8°C temperature for 0 (control) , 8, 16, and 24 hours and were evaluated for the cytomorphological changes, cell count and bacterial invasion. The finding were observed for nuclear alterations, changes in cytoplasm, bacterial invasion and cell count. Images were captured by using LeicaDM 750 microscope equipped with an ICC 50HD camera. Results: From 8 hours onwards, morphological changes were observed on both nuclear and cytoplasmic, total cell count for delayed processing time in storage temperature in sputum samples showed no significant results (p<0.05) but error bar showed reduction in number of cells, but there is increased in number of bacterial invasion. These provides evidence for the impact of processing time for storage temperature on the quality of sputum samples for cytology. Conclusion: Cytomorphological changes were observed in sputum samples that were stored in storage temperature. This can impact the laboratory results and lead to misdiagnosis. It is recommended that sputum samples should be immediately process after collection.